Alterações da função cardíaca e motilidade esofágica em pacientes com forma indeterminada da doença de Chagas - Leopoldino, Danielle Melo de (2021)
Chagas disease (CD) is currently considered the fourth disease with the greatest impact in Latin America, where individuals already infected will continue to be at potential risk of developing gastrointestinal disorders and chronic Chagas cardiomyopathy, the main cause of morbidity and mortality. Thus, we insist on the need to identify early which patients in the indeterminate and electrocardiographic form are at increased risk for the development of more severe forms. It is believed that echocardiographic assessment with assessment of myocardial deformity identifies distinct risk subgroups. The present study aimed to quantify the percentage of deformity of several myocardial segments, by measuring myocardial strain, ventricular functions and their relationship with esophageal motility, and to verify differences between chagasic individuals in the indeterminate and electrocardiographic form when compared to a group of normal individuals. Methods: Sixty-one patients underwent echocardiography with strain analysis and study of cardiac functions, as well as evaluation of esophageal motor function by high-resolution manometry in dorsal decubitus during liquid swallows. Patients with CD were divided into indeterminate (no ECG change) and electrocardiographic (any ECG change). Results: systolic function was observed preserved in the chagasic and control groups. The E'septal wave of tissue Doppler was smaller (p<0.001) and the E/E' septal ratio was greater in those with CD (p<0.001), compared to the control group: and difference between both the indeterminate (p=0,001) and electrocardiographic (p=0,001) groups in relation to controls, but with no statistical difference between the groups with CD. Longitudinal global strain was significantly reduced in the CD group compared to the control (p=0.028). Some segments showed a significant difference in the strain means between the groups with CD and control: medial anterior (p=0.033), medial lateral (p=0.012) and medial posterior (p=0.016). The strain of the medial portion of the lateral wall was lower in both the indeterminate and electrocardiographic groups compared to the control (p=0.044). In the evaluation of esophageal motility by high-resolution manometry, we observed that the amplitudes of contraction of the esophageal body at 11cm (p=0.005), 7cm (p=0.034), and 3cm (p=0.010) of the lower esophageal sphincter (LES) were smaller in patients with CD. At 11cm (p=0.02) and 3cm (p=0.030), the amplitudes were smaller in the two groups with CD compared to the control, and at 3cm from the LES, this smaller amplitude was only significant for the electrocardiographic group. Baseline LES pressure, distal contractility integral, integrated relaxation pressure and distal latencies were not different between groups. There was a positive and significant correlation between echocardiographic and manometric variables with regard to systolic, diastolic and amplitude functions, but with a low correlation coefficient. Conclusion: systolic and diastolic functions are preserved in the group with CD (clinically normal parameters), but with significantly lower mean values of E’septal and higher E/E’ ratio in patients with CD compared to our control. These parameters, and a lower degree of myocardial deformity, in addition to a smaller amplitude of esophageal contraction, may be early indicators of cardiac or esophageal involvement by CD. These results can support longitudinal studies to corroborate the function of these parameters with possible biological markers.